Not only 'the younger daughter of Dr Abdurahman': a feminist exploration of early influences on the political development of Cissie Gool - Van der Spuy, Patricia (Department of Historical Studies, 2020)
Cissie Gool was an extraordinary presence on Cape Town's political and social scene in the first half of the twentieth century. She was the first black woman to preside over a national liberatory organisation, the National Liberation League (1935), and the Non-European United Front (1938). She was the only black woman to be elected to the Cape Town City Council before 1994, where she served for 25 years. She was the first black woman to obtain a Master's Degree in Psychology at the University of Cape Town, where she studied on and off from 1918 to the year of her death, 1963. In 1962 she graduated with a BA (LLB), and was the first black woman to be invited to the Cape Bar. This thesis explores the childhood and early life of Cissie Gool. I examine influences on her political development before she became the leader of the National Liberation League in 1935. This period of her life has left few material traces. Methodologically, this thesis confronts a challenge facing those who wish to discover hidden lives in the South African past. I argue that it is possible to trace influences on such a life if one shifts the lens through which one conducts historical research. Working with a paucity of sources, where most of the people who knew Cissie Gool as a young person are deceased, this thesis searches for and highlights key influences on Gool's early personal-political development. The thesis rests on a number of premises rooted in feminist theory. I begin from the position that 'the personal is political' and take seriously the argument that the family is a key engine of historical process. I take issue with the statement in much of the secondary literature that Cissie Gool was (merely) 'the younger daughter of Dr Abdurahman', which obscures the fact that this relationship was embedded in a family, in which Cissie's mother was at least as important as her father, and where being a younger daughter with an older sister was significant too. While recognising the significance of the fact that Cissie Gool was fathered by Dr Abdurahman, I underline the centrality of women in a patriarchal society where early socialisation is the specific task of women, and where women and girls experience some degree of social segregation from men and boys. In addition to focusing the lens on family dynamics, I trace sometimes tenuous but nevertheless, real threads linking Cissie Gool to particular political circles on the left in Cape Town in the 1920s and 1930s. I suggest that the leftist heterodoxy which characterised the mature Cissie Gool may be linked to a kindred political spirit among some of her early acquaintances, specifically those at the University of Cape Town, counterposed with the more rigid orthodoxies of friends of the Communist Party on the one hand, and on the other, the so-called Trotskyite purists with whom she was linked by marriage. Cissie Gool, may have been unique in her involvement in all three circles, which intersected at socials hosted by herself and her husband, Dr A H Gool. The androcentricity of both the secondary literature and contemporary documentary sources obscures the specifics of Cissie Gool's political development in this period. Nevertheless, this thesis is based on the premise that, in the absence of more concrete sources, an exploration of the various political circles with which Cissie Gool was associated, in the wider political and socio-economic context of 1920s and 1930s Cape Town, permits one to gain insight into key influences on the political development of Cissie Gool.